2012
DOI: 10.3109/15622975.2011.615860
|View full text |Cite
|
Sign up to set email alerts
|

FoxP2is significantly associated with schizophrenia and major depression in the Chinese Han Population

Abstract: Our study indicated that the rare variant rs10447760 in FoxP2 may play an important role in schizophrenia and major depression in the Chinese Han population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 28 publications
(35 reference statements)
1
20
1
Order By: Relevance
“…The fact that SCZ patients often show language impairments such as reading difficulties [42] renders FOXP2 a plausible SCZ candidate gene. Interestingly, a previous study reported an association between genetic variation in FOXP2 and SCZ in a Han Chinese population [43]. Furthermore, Walker et al [44] identified FOXP2 as an inhibitor of the promoter activity and protein expression of DISC1 .…”
Section: Discussionmentioning
confidence: 99%
“…The fact that SCZ patients often show language impairments such as reading difficulties [42] renders FOXP2 a plausible SCZ candidate gene. Interestingly, a previous study reported an association between genetic variation in FOXP2 and SCZ in a Han Chinese population [43]. Furthermore, Walker et al [44] identified FOXP2 as an inhibitor of the promoter activity and protein expression of DISC1 .…”
Section: Discussionmentioning
confidence: 99%
“…Association of one SNP with attention deficit hyperactivity disorder (ADHD) held in only one of two cohorts tested and for only one subset of cases (131). A study of FOXP2 in >1,000 Chinese schizophrenia cases and the same number of controls reported an association for one of twelve SNPs tested (87). This variant was also associated with major depression, but not bipolar disorder.…”
Section: Making the Most Of High-throughput Technologiesmentioning
confidence: 96%
“…FAF1 (Fas Associated Factor 1) encodes a protein which binds the Fas antigen to initiate or facilitate apoptosis, amongst a wide range of other biological processes (including neuronal cell survival) (Menges, Altomare and Testa, 2009 (Giudicessi et al, 2011;Duarri et al, 2012;Lee et al, 2012), Systemic lupus erythematosus (SLE) (Y RNAs) (Kowalski and Krude, 2015), Joubert syndrome 31 and short-rib thoracic dysplasia 13 (CEP120) (Roosing et al, 2016), Amyotrophic lateral sclerosis (ALS) (FAF1) (Baron et al, 2014), Urbach-Wiethe disease (ECM1) (Hamada et al, 2003;Oyama et al, 2003), mental retardation and other cohesinopathies such as Cornelia de Lange Syndrome (STAG1) (Liu and Krantz, 2009;Lehalle et al, 2017), split hand/ split foot malformation (DYNC1I1) (Roberts et al, 1991;Tayebi et al, 2014), and a wide range of cancers (PRC1) (Li et al, 2018). Other disorders found to involve MCP-related genes include schizophrenia (FOXP2 and GABRB2) (Petryshen et al, 2005;Sanjuá et al, 2006;Lo et al, 2007;Laroche et al, 2008;Tolosa et al, 2010;Li et al, 2013;Yin et al, 2018), intellectual disability and epilepsy (GABRB2) (Srivastava et al, 2014), and neuroleptic-induced tardive dyskinesia (GABRB2) (Inada et al, 2008).…”
Section: Genes Of Interest Identified In Gwas Of Mcpmentioning
confidence: 99%